2021
DOI: 10.1002/kjm2.12404
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed circRNA and functional pathways in the hippocampus of epileptic mice based on next‐generation sequencing

Abstract: Epilepsy is a clinical syndrome caused by the highly synchronized abnormal discharge of brain neurons. It has the characteristics of paroxysmal, transient, repetitive, and stereotyped. Circular RNAs (circRNAs) are a recently discovered type of noncoding RNA with diverse cellular functions related to their excellent stability; additionally, some circRNAs can bind and regulate microRNAs (miRNAs). The present study was designed to screen the differentially expressed circRNA in an acute seizure model of epilepsy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this way, they found that mm9_circ_008777 and mm9_circ_004424 may carry out GO functions via biological regulation, metabolic processes, catalytic activity, and cellular processes, and may contribute to epilepsy through signaling pathways such as VEGF, GnRH, chemokine, and ErbB. The identification of MM9_circ_004424 and MM9_circ_008777 as potential biomarkers for epilepsy diagnosis suggests that clinical interventions targeting these circRNAs could be beneficial in the management of epilepsy 52 …”
Section: Cerna Network In Epilepsymentioning
confidence: 95%
See 2 more Smart Citations
“…In this way, they found that mm9_circ_008777 and mm9_circ_004424 may carry out GO functions via biological regulation, metabolic processes, catalytic activity, and cellular processes, and may contribute to epilepsy through signaling pathways such as VEGF, GnRH, chemokine, and ErbB. The identification of MM9_circ_004424 and MM9_circ_008777 as potential biomarkers for epilepsy diagnosis suggests that clinical interventions targeting these circRNAs could be beneficial in the management of epilepsy 52 …”
Section: Cerna Network In Epilepsymentioning
confidence: 95%
“…A prior investigation identified circUBQLN1 as being downregulated in epilepsy samples and located at chr9: 86274695-86284242. 20,52 The discovery of Y-box 7 (SOX7), a sex-determining region in epilepsy's hippocampal neurons, revealed its ability to suppress cell death. 24 Based on this data, circUBQLN1 lacked the 3′ poly(A) tail, which prevented its binding to oligo (dT) 18 primers during reverse transcription.…”
Section: Compe Titive Endog Enous Rna (Cerna )mentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of circRNAs in epilepsy patients and animal models of epilepsy is well documented, especially in TLE, and is primarily associated with subsequent miRNA dysregulation. [59][60][61] As with miRNA-targeted RNA drugs, therapeutic modulation of circRNAs is based on either upregulation using synthetic circRNAs or downregulation using either siRNAs or ASOs, 53 but so far only two studies have reported on circRNA interference in epilepsy (Table 1). In the first study, an siRNA against circIgf1r was injected ICV into mice, 2 days prior to SE induced by 4-aminopyridine.…”
Section: Noncoding Rnas Are Promising Targets For the Treatment Of Ac...mentioning
confidence: 99%
“…Therefore, dysregulated miRNA profiles in biofluids may be potentially useful biomarkers in people with drug-resistant TLE [ 11 , 12 ]. Regarding circulating microRNAs (c-miRNAs), altered levels have also been found in epilepsy patients [ 13 , 14 ] and in animal models of epilepsy, especially in TLE [ 15 , 16 ]. Through this literature review, the authors aim to provide a comprehensive synthesis of the current understanding of dysregulated c-miRNAs in TLE, with a focus on their potential capability of providing disease modification and counteracting drug resistance in TLE.…”
Section: Introductionmentioning
confidence: 99%